BUSINESS NETWORKS IN E-COMMERCE INTERNATIONALIZATION –Two Finnish Companies Targeting Russia - Helle, Niko (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
With the proliferation of Internet, online shopping has become an increasingly essential part of global economy and thus, increasingly important field of research. While the internationalization process of a company has for long been in the focus of academic research, internationalization of e-commerce is a much newer field of study. The earlier empirical research has amply pointed out the difficulties of traditional internationalization models to explain the internationalization process of e-commerce companies. Conversely, business networks have been argued to play a major role in the e-commerce internationalization. The purpose of this study is to study how business networks influence the internationalization process of e-commerce companies. Conducted as a case study, this research studies the internationalization process of two Finnish e-commerce companies, Hong Kong and Hifi Studio, into possibly one of the most booming online markets - Russia. The empirical findings of the study concur with the earlier literature. The observed internationalization process differs from the assumptions of traditional international business models, and business networks are found influential for the process. However, the behavior of the two studied organizations is observed more independent than the network view to internationalization presumes. The trigger to internationalize rises from within the organizations and market potential is the primary explanation for selection of target markets. No network relationships were found to have an effect on foreign market selection, nor selection of mode of operations. This study indicates that exploring foreign markets is actually about investing in specific relationships within a business network, rather than overcoming economic, institutional, and cultural barriers. Companies utilize a wide array of relationships in their internationalization process and may effectively overcome disadvantages of operating in a foreign market by adopting partnerships with correct partners. However, building and maintaining operational business relationships is a demanding process, and organizations should prefer quality over quantity in their partner selection. Moreover, relationships where the focal party possess significant influence and leverage over other actor should be favored. Lastly, relationships need to be continuously evaluated and assessed in comparison with strategic business goals. Ultimately, e-commerce can be considered a new, low-risk, cost-effective, and relationship-oriented internationalization method, suitable especially in volatile market conditions as Russia today. This revolutionary new mode of international business activity calls for more profound focus of business managers and academia alike, as its weight on global trade continues to grow.